Pengaruh Penambahan Lawi-Lawi (Caulerpa Sp) terhadap Karakteristik Produk Selai Nanas (Ananas Eomosus) - Moh. Jamal H. Podungge; Lukman Mile; Nikmawatisusanti Yusuf (Transbahasa, 2024)
This research aims to determine the formula and level of panelists' preferences as well as the chemical quality of pineapple jam with the addition of lawi-lawi. The treatment in the research was the addition of lawi-lawi with concentrations of A (75%), B (50%) and C (25%). The organoleptic data obtained was processed using Kruskall Wallis analysis and chemical data using a Simple Completely Randomized Design. Further test results use Duncan's advanced test. The results of the research showed that the pineapple jam formula obtained was by adding different lawsi-lawi: A (75%), B (50%) and C (25%) with the other ingredients used being the same (pineapple 100g, sugar 65g and citric acid 0.2g). Panelists preferred pineapple jam with the addition of 75% lawi-lawi (formula B). Pineapple jam formula A (75% lawi-lawi), has chemical quality characteristics; sugar content 60.20%, viscosity 1875cp, dissolved solids 65.20% and calcium 1.04%. Formula B (50% lawi-lawi) has a sugar content of 57.70%, viscosity of 900cp, soluble solids of 65.61% and calcium of 1.02%. Formula C (25% lawi-lawi) has a sugar content of 51.68, a viscosity of 550cp, soluble solids of 67.13% and calcium of 0.94%. This study shows that pineapple jam with a 75% addition of lawi-lawi (formula A) is most preferred by panelists and has good chemical quality. Overall, the addition of lawi-lawi at various concentrations affects the organoleptic and chemical characteristics of pineapple jam, with the best results at a 75% concentration.